The effect stimulation of sensitive skin areas by temperature on vegetative indices at dosage exercise stress (Experimental biology, 2015)
The research revealed that an adequate temperature impact test on heat-sensitive zone result in a relatively rapidrecovery all the investigated of indicators after treadmill test. As a result of thermal stimulation of the skin zones areimproving the functional condition of the organism, raises performance capacity both healthy people and patients withabnormalities of the cardiovascular system.
Keywords: temperature; exercise stress